Bictegravir/emtricitabine/tenofovir alafenamide in clinical practice for people with HIV: final 24-month effectiveness and safety outcomes in key populations in the observational BICSTaR cohort - Trottier, Benoit; Yang, Chia-Jui; Watanabe, Dai; Marchetti, Giulia; Elbirt, Daniel; De Barra, Eoghan; Gündüz, Alper; Lee, Sun Hee; Vogelmann, Roger; Robineau, Olivier; Choy, Chiaw Yee; Berrevoets, Marvin; et al. (HIV research & clinical practice, 2025)
Background: BICtegravir Single Tablet Regimen (BICSTaR) is an observational cohort study evaluating the effectiveness and safety of bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) in treatment-naïve (TN) and treatment-experienced (TE) people with HIV. Objective: To present final pooled 24-month outcomes for the full cohort. Methods: Prospective data were pooled from TN and TE adults with HIV initiating B/F/TAF in routine clinical practice across 14 countries (data collection: 25/06/2018-29/12/2023). Outcomes at 24 months included virologic suppression (HIV-1 RNA <50 copies/mL), immunologic effectiveness (change in CD4 cell count and CD4/CD8 ratio), persistence, and safety. Outcomes were also analysed in key populations. Results: Of 2,074 (483 TN, 1,591 TE) participants included, most were male (85%), White (70%), and had ≥1 comorbidity (66%). Median (Q1, Q3) age was 45 (35, 54) years. At 24 months, 94% of TN and 96% of TE participants had HIV-1 RNA <50 copies/mL (missing = excluded analysis). These values were 88% and 86%, respectively, in a discontinuation = failure analysis. Effectiveness remained high across all key populations at 24 months. Median (Q1, Q3) CD4 count increased by 257 (127, 447) cells/µL in TN and 40 (-70, 153) cells/µL in TE participants (both p < 0.001). There was no reported treatment-emergent resistance to B/F/TAF. Persistence was high at 24 months (TN, 95%; TE, 91%). Drug-related adverse events occurred in 11% of TN and 12% of TE participants, leading to B/F/TAF discontinuation in 5%. Conclusions: B/F/TAF was generally well tolerated over 24 months, with high effectiveness and persistence observed among a broad range of people with HIV.
Gesehen am 07.07.2025